Re-expression of nestin in the myocardium of postinfarcted patients - Mokry, J; Pudil, R; Ehrmann, J; Cizkova, D; Osterreicher, J; Filip, S; Kolar, Z (Virchows Archiv, 2008)
Intact cardiac muscle cells in the adult heart do not express intermediate filament nestin. In this study, we report on widespread expression of intermediate filament nestin in human myocardium of patients who died from the myocardial infarction. Nestin was detected in cardiomyocytes, endothelial cells, and few interstitial cells. Elevated levels of nestin were observed in cardiac muscle cells in all specimens, although the intensity of immunoreactivity and distribution of the signal differed. The strongest immunoreactivity was observed from 4 days after myocardial infarction in the infarction border zone where nestin was distributed homogeneously in the entire sarcoplasm of cardiac muscle cells. Within the following week, nestin in immunoreactive cardiomyocytes was redistributed and restricted to small subsarcolemmal foci and to intercalated discs. Angiogenic capillaries that grew between vital nestin-positive cardiomyocytes and entered the necrotic area expressed also high levels of nestin. Nestin-positive endothelial cells were often observed in mutual interactions with nestin-positive cardiac muscle cells. These findings document a crucial role of nestin in remodeling cytoskeleton of cells in the human postinfarcted myocardium.
Keywords: Intermediate Filaments; proteiny nervové tkáně; cytoskelet; Humans; Case-Control Studies; Intermediate Filament Proteins; lidé středního věku; Nerve Tissue Proteins; regulace genové exprese; studie případů a kontrol; kardiomyocyty; Female; Aged; dospělí; Nestin; senioři; lidé; intermediární filamenta; Myocytes, Cardiac; proteiny intermediálních filament; infarkt myokardu; Adult; ženské pohlaví; Gene Expression Regulation; Male; Middle Aged; Myocardial Infarction; nestin; Aged, 80 and over; senioři nad 80 let; myokard; Myocardium; mužské pohlaví; Cytoskeleton